1972
DOI: 10.1021/i160044a026
|View full text |Cite
|
Sign up to set email alerts
|

Apparatus for the Determination of the Solubility of Hydrogen in Molten Salts

Abstract: A two-chamber apparatus has been developed for the determination of the solubility of hydrogen in molten salts over wide ranges of temperature and pressure. Illustrative data are presented for the solubilities of helium and hydrogen in a LiF-BeFa eutectic at 600°C. Literature Cited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Previous studies by Malinauskas, et al (1972), indicated a linear dependence of solubility on saturation pressure for the systems under consideration. Similarly, this Henry's law behavior was observed by Watson, et al (1962), for the solubilities of helium, neon, argon, and xenon in a closely related solvent (a 64 mol % LiF-36 mol % BeF2 eutectic).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies by Malinauskas, et al (1972), indicated a linear dependence of solubility on saturation pressure for the systems under consideration. Similarly, this Henry's law behavior was observed by Watson, et al (1962), for the solubilities of helium, neon, argon, and xenon in a closely related solvent (a 64 mol % LiF-36 mol % BeF2 eutectic).…”
Section: Resultsmentioning
confidence: 86%
“…The apparatus and the experimental procedure that were employed in this work have been described previously (Malinauskas, et al, 1972). The apparatus consisted of two double-walled vessels which were positioned within separate furnaces and could be isolated from one another, or interconnected, through the manipulation of a freeze valve.…”
Section: Experimental Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen in metal is assumed to be in the atomic state. On the other hand, hydrogen in a molten salt solution is thought to dissolve as a hydrogen molecule, 15 and Henry's law should define the solubility of hydrogen in the molten salt.…”
Section: General Voltammetric Behavior Of Hydrogen Reduction-fig-mentioning
confidence: 99%
“…Based on the analysis of hydrogen reduction, the following two processes are expected to proceed in parallel during the potential sweeps, as shown in Fig. 8 2H Hydrogen in molten salt solution is thought to dissolve as hydrogen molecules, 16 and Henry's law should define the solubility of hydrogen in the melt. Hydride ions ͑Red͒ and hydrogen molecules ͑Ox͒ in the melt behave as the usual reactants and products in a surface redox process: hydride ions diffuse to the electrode surface and are oxidized to hydrogen molecules, probably via adsorbed hydrogen atoms ͑process 4͒.…”
Section: Resultsmentioning
confidence: 99%